Origin of calderas: discriminating between collapses and explosions - Izumi Yokoyama (Annals of Geophysics, 2017)
Origins of calderas may differ according to their subsurface structure that may be characterized by high or low density deposits that may be observed as high or low gravity anomalies, respectively. In the Introduction, the pioneering work of Fouqué[1879] on Santorini caldera is referred to in relation to definition of calderas. First, our discussion is focused on four calderas that were seen forming during the period from 1815 (the Tambora eruption) to 1991 (the Pinatubo eruption). Coincidently, these four calderas are all low-gravity-anomaly type. Their formation processes and subsurface structure are summarized by the existing data analyzed by various authors. These results are confirmed by results of drillings at some other calderas. Then, caldera formation of both types is discussed: High-gravity-anomaly-type calderas are expected to originate from subsidence of high-density ejecta into the summit magma reservoir. On the calderas of this type, the genetic eruptions believed to be accompanied by subsidences were not actually observed, and consequently three examples are mentioned only briefly. The low-gravity-anomaly-type calderas are discussed from standpoint of both the models of collapses and explosions. It is also emphasized that dynamic pressure ofexplosions is an important factor in the caldera formation, not only volume of the ejecta. To confirm the possibility that volcanic ejecta and edifices collapse into magma reservoirs, we discuss stress propagation from a depleted reservoir upward towards the Earth surface. Formation mechanisms of large calderas of this type are speculated; large calderas measuring about 20 km across may develop by successive merging of component calderas over a long period of times. A Kamchatka caldera under enlargement during the Holocene period is interpreted by successive merging of five component calderas.